Acute Bacterial Sinusitis Complicating Viral Upper Respiratory Tract Infection in Young Children. (2nd September 2014) - Marom, Tal; Alvarez, Pedro E.; Jennings, Kristofer; Patel, Janak A.; McCormick, David; Chonmaitree, Tasnee
Abstract : Objectives: (1) Analyze the clinical characteristics of upper respiratory infections (URIs) complicated by acute bacterial sinusitis (ABS) in young children. (2) Describe the bacteria and viruses isolated in nasopharyngeal specimens in children with ABS. Methods: We identified ABS episodes in a prospective, longitudinal cohort study of 294 children (aged 6‐35 months at enrollment), who were followed up for one year to capture all URI episodes and complications. At the initial URI visit (median day = 4), nasopharyngeal samples were obtained for bacterial cultures and viral studies. The study was conducted at the University of Texas Medical Branch, Galveston, during 2003‐2007. Results: Of 1295 documented URI episodes, 103 (8%) episodes (in 73 children) were complicated by ABS, 32 of which were concurrent with acute otitis media. The majority (72%) of ABS episodes were diagnosed based on persistent symptoms or a biphasic course. The average age was 18.8 ± 7.2 months; white children were more likely to have ABS episodes than blacks ( P =. 01). Viruses were detected in 63% during the initial URI visit; rhinovirus detection was positively correlated with ABS ( P =. 01). Bacterial cultures were positive in 82/83 (99%) available samples; polymicrobial (56%), Moraxella catarrhalis (20%) and Streptococcus pneumoniae (10%) were the most common cultures. Presence of pathogenic bacteria overall and presence of M. catarrhalis during URI were positively correlated with ABS risk ( P =. 04 for both). Conclusions: ABS complicates 8% of URIs in children. Girls have more frequent ABS episodes than boys. Presence of rhinovirus and M catarrhalis during URI are positively correlated with ABS risk.